Pollution Problem in River Kabul: Accumulation Estimates of Heavy Metals in Native Fish Species. (3rd August 2015) - Ahmad, Habib; Yousafzai, Ali Muhammad; Siraj, Muhammad; Ahmad, Rashid; Ahmad, Israr; Nadeem, Muhammad Shahid; Ahmad, Waqar; Akbar, Nazia; Muhammad, Khushi
Abstract : The contamination of aquatic systems with heavy metals is affecting the fish population and hence results in a decline of productivity rate. River Kabul is a transcountry river originating at Paghman province in Afghanistan and inters in Khyber Pakhtunkhwa province of Pakistan and it is the major source of irrigation and more than 54 fish species have been reported in the river. Present study aimed at the estimation of heavy metals load in the fish living in River Kabul. Heavy metals including chromium, nickel, copper, zinc, cadmium, and lead were determined through atomic absorption spectrophotometer after tissue digestion by adopting standard procedures. Concentrations of these metals were recorded in muscles and liver of five native fish species, namely, Wallago attu, Aorichthys seenghala, Cyprinus carpio, Labeo dyocheilus, and Ompok bimaculatus . The concentrations of chromium, nickel, copper, zinc, and lead were higher in both of the tissues, whereas the concentration of cadmium was comparatively low. However, the concentration of metals was exceeding the RDA (Recommended Dietary Allowance of USA) limits. Hence, continuous fish consumption may create health problems for the consumers. The results of the present study are alarming and suggest implementing environmental laws and initiation of a biomonitoring program of the river.